posted by Anonymous .
Hi I need help with another balancing oxidation-reduction reaction:
Cu(s) + Ag^1+(aq) → Cu^2+(aq) + Ag(s)
Cu (s) --> Cu^2+ (aq) + 2e-
2 [1e +Ag^1+ (aq) --> Ag(s)]
Cu(s) + 2 Ag(aq) --> Cu (aq) + 2 Ag (s)
Is this right?
And I need help with this one...
Zn(s) + H2SO4(aq) → ZnSO4(aq) + H2(g)
Very good except you omitted a charge on the Ag, left side. You had it on the preceding step; you just didn't carry it forward.
Cu(s) + 2Ag^+(aq) ==> etc.
The second one is balanced as is, isn't it.